Integrating phylogenomic and population genomic patterns in avian lice provides a more complete picture of parasite evolution. (24th November 2017) - Sweet, Andrew D.; Boyd, Bret M.; Allen, Julie M.; Villa, Scott M.; Valim, Michel P.; Rivera‐Parra, Jose L.; Wilson, Robert E.; Johnson, Kevin P.
Abstract: Parasite diversity accounts for most of the biodiversity on earth, and is shaped by many processes (e.g., cospeciation, host switching). To identify the effects of the processes that shape parasite diversity, it is ideal to incorporate both deep (phylogenetic) and shallow (population) perspectives. To this end, we developed a novel workflow to obtain phylogenetic and population genetic data from whole genome sequences of body lice parasitizing New World ground‐doves. Phylogenies from these data showed consistent, highly resolved species‐level relationships for the lice. By comparing the louse and ground‐dove phylogenies, we found that over long‐term evolutionary scales their phylogenies were largely congruent. Many louse lineages (both species and populations) also demonstrated high host‐specificity, suggesting ground‐dove divergence is a primary driver of their parasites' diversity. However, the few louse taxa that are generalists are structured according to biogeography at the population level. This suggests dispersal among sympatric hosts has some effect on body louse diversity, but over deeper time scales the parasites eventually sort according to host species. Overall, our results demonstrate that multiple factors explain the patterns of diversity in this group of parasites, and that the effects of these factors can vary over different evolutionary scales. The integrative approach we employed was crucial for uncovering these patterns, and should be broadly applicable to other studies.